Technological integration of virtual surgical planning, surgical navigation, endoscopic support and patient-specific implant in orbital trauma (2020)
Currently, we have different technologies and techniques that improve the results in orbital trauma. However, there are few studies that study the technological integration in orbital trauma and the synergism of all the techniques. For this reason, the objective of this case is to illustrate the management of orbital trauma by integrating endoscopic support, virtual surgical navigation, patient-specific implant, virtual surgical planning in the management of a sequel due to insufficient reconstruction of orbital volume.